2020
DOI: 10.1097/bpo.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes Following Vickers Ligament Release and Growth Modulation for the Treatment of Madelung Deformity

Abstract: Background: Madelung deformity arises from a partial distal radial growth disturbance in combination with an abnormal hypertrophic ligament spanning the volar radius and carpus, termed, the Vickers ligament. The purpose of this study is to report long-term clinical and radiographic outcomes following Vickers ligament release and distal radial physiolysis in a population of skeletally immature patients with symptomatic Madelung deformity. Methods: Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…While our cohort of patients included some older patients for whom a corrective osteotomy was performed, the presence or absence of Vickers' ligament might be of interest in children 8 to 10 years old for whom a physiolysis might prevent the aforementioned deformation. Although various studies have reported good clinical and radiographic outcomes after Vickers' ligament release/un-tethering with physeal resection or radial dome osteotomy (Del Core et al, 2020;Otte et al, 2019;Steinmann et al, 2013), these and other studies have failed to report the presence of this particular structure. Moreover, the presence of a Vickers' ligament might cause a more severe course of the deformity's progression.…”
Section: Discussionmentioning
confidence: 99%
“…While our cohort of patients included some older patients for whom a corrective osteotomy was performed, the presence or absence of Vickers' ligament might be of interest in children 8 to 10 years old for whom a physiolysis might prevent the aforementioned deformation. Although various studies have reported good clinical and radiographic outcomes after Vickers' ligament release/un-tethering with physeal resection or radial dome osteotomy (Del Core et al, 2020;Otte et al, 2019;Steinmann et al, 2013), these and other studies have failed to report the presence of this particular structure. Moreover, the presence of a Vickers' ligament might cause a more severe course of the deformity's progression.…”
Section: Discussionmentioning
confidence: 99%
“…Some benefits of these procedures have been reported; however, simultaneous ulnar shortening or additional secondary surgeries were needed due to residual deformities. [2][3][4][5] It is difficult to predict how much growth can be regained only by these procedures because the influence on the growth plate starts at birth. Presently, the treatment modality for Madelung deformity is quite different from that for posttraumatic growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, various surgical interventions, such as corrective osteotomy, Vickers ligament release, and ulnar shortening, have been attempted. [1][2][3][4][5][6][7][8][9] However, all these procedures can only reduce the severity of the deformity and pain without preventing the development of physeal disorders. Herein, we report a case of an adolescent patient with severe forearm deformity in whom we performed callus distraction with corrective osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of Vickers ligament is consequently crucial to growth modulation and improvement of symptoms in this cohort of patients. 45 Similarly, for preoperative planning of syndactyly and polydactyly correction, assessment of adjacent soft tissue structures, including tendons, ligaments, pulleys, and volar plates, aids the surgeons in determining which bony structures to sacrifice and which need to be reconstructed and reattached.…”
Section: Clinical Applications Of 3d Mri Of the Hand And Wristmentioning
confidence: 99%